A crack identification microwave procedure based on a genetic algorithm for nondestructive testing. - Caorsi, S. (IEEE Transactions on antennas and propagation)
This paper is aimed at exploring the possibility of using a microwave approach based on a genetic algorithm to detect a defect inside a known host object. Starting from the knowledge of the scattered field, the problem solution is recast as a two-step procedure. After defining a cost function depending on the geometric parameters of the crack, a minimization procedure based on a hybrid-coded genetic algorithm is applied. The influence of the noise as well as of the geometry of the defect on the crack detection and reconstruction is investigated. Moreover, the numerical effectiveness of the iterative approach is examined